Lignocellulosic biofuels – Challenges and potentials - K. KASTHURAIAH; N. SAI KISHORE (International Journal of Pharma and Bio Sciences, 2017)
Lignocellulosic biomass consist of inedible parts of woody grass plants, stalk of sweet sorghum and agricultural residues, are the sources for the 2nd generation biofuels. Lignocellulosic biomass comprises of many different polysaccharides cellulose, hemicelluloses, phenolic polymer lignin and proteins. The problem of the 2nd generation feed stock is the extraction of the sugars located inside the lignin and cellulose structure. To convert lignocellulosic biomass to biofuels the complex polysaccharides and lignin must be broken down or hydrolysed into simple sugars. This process of bioconversion of cellulose to ethanol involves pre-treatment, saccharification and fermentation. The other challenges include types of the biomass and their availability round the year, logistics, and production technologies. These challenges take in identification and improvement of energy crops like sweet sorghum, switch grass, miscanthus, alfa alfa, etc., by biotechnological approaches by generating feed stocks with low lignin content and modified traits which can tolerate biotic and abiotic stresses with improved cellulose content. Down regulation of key enzymes involved in lignin biosynthetic pathway may be a promising approach to decrease or alter the hard lignin content in lignocellulosic feed stock materials. With the advent of genetic engineering and crop improvement strategies in energy crops may provide continuous supply of feed stock for the production of biofuels as an alternative source of energy. To benefit the environment and also to meet the global demand of fossil fuels, the biofuels produced from lignocellulosic biomaterial by biotechnological route may help in decreasing the emission of green house gasses and also save our food crops.